Photoablation at single cell resolution and its application in the Drosophila epidermis and peripheral nervous system - Mangione, Federica; D’Antuono, Rocco; Tapon, Nicolas (Frontiers in Physiology, 2023)
Tissues contain diverse cell populations that, together, make up physiologically functional units. A remarkable example is the animal epidermis, where neuronal and non-neuronal cells intermingle to allow somatosensory perception. In the peripheral nervous system (PNS), the tight association between heterogenous cell types poses challenges when the structural and physiological contributions of neuronal and surrounding cells need to be dissected with suitable precision. When genetic tools for cell-specific, spatiotemporally controlled gene expression are not available, targeted cell ablation represents a considerable obstacle. Here, we describe an efficient method to overcome this limitation and demonstrate its application to the study of the differentiating Drosophila epidermis and PNS. This methodology relies on the use of near infrared (NIR) femtosecond (fs) laser pulses for ablation of the desired cells at the desired time. We show how to confine the photodamage to the targeted cell to induce its death, without harming neighbouring tissues or structures. We validated our approach in the Drosophila PNS by studying the responses of photo-ablated neurons, non-neuronal cells, and the surrounding epidermis. Diverse cellular behaviours including cell extrusion, cell rearrangements and cell shape changes can be monitored in vivo immediately after damage, as well as for several hours post-ablation with high optical resolution using confocal microscopy. This methodology provides a flexible tool to ablate individual cells with high precision and study morphological responses to cell loss in targeted areas or neighbouring structures. We anticipate that this protocol can be easily adapted to other model systems and tissues.